Does greater patient involvement in healthcare decision-making affect malpractice complaints? A large case vignette survey. - Søren Birkeland (Public Library of Science (PLoS), 2021)
Background Although research findings consistently find poor communication about medical procedures to be a key predictor of patient complaints, compensation claims, and malpractice lawsuits ("complaints"), there is insufficient evidence to determine if greater patient involvement could actually affect the inclination to complain. Objectives We conducted an experimental case vignette survey that explores whether greater patient involvement in decision-making is likely to influence the intention to complain given different decisions and consequences. Methods Randomized, national case vignette survey with various levels of patient involvement, decisions, and outcomes in a representative Danish sample of men. We used prostate specific antigen (PSA) screening in men aged 45 to 70 years as the intervention illustrated in 30 different versions of a mock clinical encounter. Versions differed in the amount of patient involvement, the decision made (PSA test or no PSA test), and the clinical outcomes (no cancer detected, detection of treatable cancer, and detection of non-treatable cancer). We measured respondents' inclination to complain about care in response to the scenarios on a 5-point Likert scale (from 1: very unlikely to 5: very likely). Results The response rate was 30% (6,756 of 22,288). Across all scenarios, the likelihood of complaint increased if the clinical outcome was poor (untreatable cancer). Compared with scenarios that involved shared decision-making (SDM), neutral information, or nudging in favor of screening, the urge to complain increased if the patient was excluded from decision-making or if the doctor had nudged the patient to decline screening (mean Likert differences .12 to .16, p < .001). With neutral involvement or nudging in favor of intervention, the desire to complain depended highly on the decision reached and on the patient's course. This dependence was smaller with SDM. Conclusions Greater patient involvement in decision-making appears to be associated with less intention to complain about health care, with SDM resulting in the greatest reduction in complaint likelihood.